1988
DOI: 10.1021/ie00075a005
|View full text |Cite
|
Sign up to set email alerts
|

Alkylation of isobutane with C4 olefins. 3. Two-step process using sulfuric acid as catalyst

Abstract: Operating conditions for both the first step and the second step of the two-step process greatly affect alkylate quality and yields; statistical analyses indicate preferred conditions. With n-butenes as olefins, alkylates with research octane number (RON) values in the 99-100.5 range can be produced at operating conditions that are unacceptable in a one-step process. The isoparaffins in the alkylates are produced by three chemical mechanisms, and the relative importance of each differs with the RON of the alky… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
54
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 6 publications
3
54
1
Order By: Relevance
“…This route was similar to the mechanism of the H 2 SO 4 -catalyzed system . In the alkylate, TMP-123 (with molecular weight 123; C 8 H 9 D 9 ) was detected, which could be due to the direct alkylation between deuterated isobutane and 2-butene.…”
Section: Mechanism Of Alkylation Reactionssupporting
confidence: 67%
See 1 more Smart Citation
“…This route was similar to the mechanism of the H 2 SO 4 -catalyzed system . In the alkylate, TMP-123 (with molecular weight 123; C 8 H 9 D 9 ) was detected, which could be due to the direct alkylation between deuterated isobutane and 2-butene.…”
Section: Mechanism Of Alkylation Reactionssupporting
confidence: 67%
“…The tert -butyl carbocation reacts with 2-butene quickly to form the TMP carbocation, which then is converted to TMP (major product in alkylate) via hydride transfer from isobutane, and the tert -butyl carbocation is restored. In the intermediate step, TMP carbocation can isomerize and form different forms of TMPs through hydride and methyl shifts. Wang et al studied the C 4 alkylation mechanism using density functional theory and found the stability of TMP cations (2,2,4- sec -TMP + > 2,3,4- tert -TMP + > 2,2,3- tert -TMP + ) trend in accordance with the TMPs selectivity in the obtained alkylate …”
Section: Mechanism Of Alkylation Reactionsmentioning
confidence: 96%
“…Therefore, it is conclusive that low temperatures are favorable for the alkylation of isobutane/2-butene catalyzed by the BMIC-2AlCl 3 /thioalcohol ionic liquid. This characteristic is similar to the alkylation catalyzed by sulfuric acid [31,32] or aluminium chloride [24].…”
Section: Effect Of Temperaturementioning
confidence: 58%
“…Alkylate, produced by the C4 alkylation reaction, has the advantages of a high octane number, low vapor pressure, very low sulfur content, and cleaning combustion, which is recognized as an ideal blending component for gas upgrading . Currently, commercial alkylation processes are primarily catalyzed by concentrated sulfuric acid (H 2 SO 4 ) and hydrofluoric acid (HF). , However, the HF catalyst has high toxicity, high volatility, and potential safety hazards, and the H 2 SO 4 -catalyzed process suffers from high catalyst consumption, equipment corrosion, and environmental pollution. , To cope with these issues of liquid catalysts, various solid acids were investigated as the catalyst for alkylation, including sulfated zirconia, , heteropolyacids, , acid resins, chlorinated alumina, and the most commonly used acidic zeolites. …”
Section: Introductionmentioning
confidence: 99%